THE INFLUENCE OF AGE AND GENDER ON THE LEVEL OF MICRONUCLEI IN THE EXFOLIATED ORAL MUCOUS CELLS IN HEALTHY PERSONS OF ARMENIAN POPULATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Influence of age and gender on the levels of cytogenetic disturbances in exfoliated oral mucous cells of healthy non-smoking Armenians by means of micronucleus assay is analysed. It is revealed the increase of the micronuclei levels of women (compared with men) and of older persons (compared with younger ones).
Keywords: levels of cytogenetic disturbances i; age and gender; oral mucous cells; non-smoking